QUALITY MANAGEMENT OF ECOTOURISM PRODUCT - Todorov, Predrag (The Business of Tourism, 2025)
Abstract: Quality management of eco-tourism products is a key aspect of sustainable tourism development that increasingly focuses on the preservation of natural resources and the enhancement of tourist experiences. This paper explores the importance of effective quality management through the application of eco-management systems, such as EMAS and ISO standards, which provide a framework for improving ecological performance and sustainability. Focusing on the integration of sustainability into the creation of ecotourism products, the paper analyzes key steps, including natural resource assessment, planning of ecological activities, collaboration with local communities, and tourist education. The implementation of these strategies not only contributes to environmental conservation but also enhances tourist satisfaction and awareness of the importance of responsible behavior. Additionally, the paper highlights the challenges and opportunities faced by tourist destinations in adopting these approaches, emphasizing the need for continuous improvement and innovation. This paper provides recommendations for effective quality management in ecotourism, thereby empowering local communities and promoting the long-term sustainability of tourist destinations. Key words: quality management, EMAS and ISO standards, eco-management system, ecotourism, tourist product.